Implementation of Assignment-Assisted Video-Based Online Learning to Increase the Intelligent Character Values of Physics Teacher Candidates - Andi Arie Andriani; Riskawati Riskawati; Dewi Hikmah Marisda (Universitas Lambung Mangkurat, 2023)
This research was motivated by the ineffectiveness of learning physics during the pandemic. Subject lecturers apply a solution to learning, namely implementing assignment-assisted video-based learning. This study aimed to increase the value of the intelligent character of physics teacher candidate students. This research is classroom action research that consists of two cycles. The research subjects were ten physics teacher candidates teaching optical physics courses. The research instruments used were student character observation sheets and intelligence tests. Data analysis techniques using descriptive statistical analysis. The results showed increased acquisition of intelligent character scores for physics teacher candidates in each cycle. The highest increase is in grade II in the range of 75-95. The conclusion that can be drawn from this research is that implementing assignment-assisted video-based online learning can increase the intelligence character scores of prospective physics teacher students and is at grade II in the range 75-95 (above average intelligence). This research provides an overview of learning innovations for teachers for classroom application in physics learning. By implementing learning videos, students were actively involved in constructing knowledge, attitudes, and skills both personally and in groups, so the implication of implementing video-based learning assignments was to create a young generation with character in the development of science, technology, and society, where students have been able to implement character values in applying online learning technology. In this case, the student has high integrity and character based on Islamic and Muhammadiyah values.